High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.